2011
DOI: 10.3389/fpsyg.2011.00229
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning of Two Artificial Languages Presented Successively: How Conscious?

Abstract: Statistical learning is assumed to occur automatically and implicitly, but little is known about the extent to which the representations acquired over training are available to conscious awareness. In this study, we focus on whether the knowledge acquired in a statistical learning situation is available to conscious control. Participants were first exposed to an artificial language presented auditorily. Immediately thereafter, they were exposed to a second artificial language. Both languages were composed of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 56 publications
3
50
2
Order By: Relevance
“…By this account, learners who most strongly acquired the word structure of L1 would most egregiously mis-segment L2, at least initially. On the other hand, the observed negative relationship between L1 and L2 learning is contrary to evidence collected by Franco, Cleeremans, and Destrebecqz (2011) that the weakest L1 learners tended to also be the weakest L2 learners. Despite their dissimilar conclusions, both Perruchet et al (2014) and Franco et al (2011) investigated learning only when participants were explicitly cued to the presence of two languages (i.e., in instruction, voicing, or a combination of the two).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By this account, learners who most strongly acquired the word structure of L1 would most egregiously mis-segment L2, at least initially. On the other hand, the observed negative relationship between L1 and L2 learning is contrary to evidence collected by Franco, Cleeremans, and Destrebecqz (2011) that the weakest L1 learners tended to also be the weakest L2 learners. Despite their dissimilar conclusions, both Perruchet et al (2014) and Franco et al (2011) investigated learning only when participants were explicitly cued to the presence of two languages (i.e., in instruction, voicing, or a combination of the two).…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the observed negative relationship between L1 and L2 learning is contrary to evidence collected by Franco, Cleeremans, and Destrebecqz (2011) that the weakest L1 learners tended to also be the weakest L2 learners. Despite their dissimilar conclusions, both Perruchet et al (2014) and Franco et al (2011) investigated learning only when participants were explicitly cued to the presence of two languages (i.e., in instruction, voicing, or a combination of the two). In the present case, learners were informed only of a single language, suggesting that the negative correlation between L1 and L2 knowledge may be influenced by learners’ expectations about the number of structures in their environment.…”
Section: Discussioncontrasting
confidence: 99%
“…The same procedure but with the streams of the other two conditions was used in the second session. Franco, Cleeremans, and Destrebecqz (2011) showed that people are able to learn two artificial languages sequentially and to easily differentiate between them. Gebhart, Aslin, and Newport (2009) found interference between statistically coherent languages when they were presented sequentially, but the interference disappears if either the exposure to the second language was long enough, or the presence of two different structures was marked explicitly in the instructions, or when the two subsequent languages were separated by a pause.…”
Section: Methodsmentioning
confidence: 99%
“…First, there is evidence that although statistical learning occurs incidentally or implicitly, it produces knowledge that is at least partially explicit in nature, at least in adult learners (Franco et al 2011;Bertels et al 2012Bertels et al , 2013Batterink et al 2015). Whereas implicit knowledge, such as abstract grammar knowledge (Reber 1967) or perceptual-motor skills (Cohen and Squire 1980) must be acquired over time through direct experience, one feature of explicit knowledge is that it can be provided to learners through explicit instruction (i.e., by verbally transmitting information from one person to another).…”
mentioning
confidence: 99%